Effects of conductive polymers (type and concentration) in coatings with zinc particles of different shapes - Kohl, Miroslav; Kalendová, Andréa; Deshpande, P. P.; Schmidová, Eva (Springer, 2019)
The objective of this work was to compare the anticorrosion effects of organic coatings containing zinc metal consisting of either lamellar particles or isometric particles and to reduce the zinc metal content of the coatings while preserving their high anticorrosion efficiency. The optimization and Zn metal content reduction can be achieved using zinc with a lamellar particle shape and application of conductive polymers. Conductive polymers are expected to enhance the electrochemical effect of zinc metal in paints. Organic coatings with lamellar zinc particles also exhibit better mechanical properties. Optimization of the amount of zinc lamellar particles could promote a wider use of this material in anticorrosion paints. The conductive polymers used in this work included polyaniline phosphate, polyaniline benzoate, and carbonized polyaniline. A solvent-based epoxy-ester resin served as the binder. Model paints consisting of this resin and containing different concentrations of polyaniline phosphate, polyaniline benzoate, and carbonized polyaniline were prepared. The paints were tested at the critical pigment volume concentration (CPVC) of Zn dust and at lower Zn dust concentrations, specifically 2% below the CPVC. The paints containing combinations of zinc and a conductive polymer contained the sum of the pigments just below the CPVC of the zinc dust species used. This implies a level of 39% of (PVCZn-lam) for the systems with lamellar zinc and a level of 61% of (PVCZn-sf) for the systems with spherical zinc. The pigment volume concentration (PVC) of the conductive polymers in the zinc-containing paints was (based on results obtained previously) 1%, 5%, and 10% in the systems with lamellar zinc and 1%, 5%, 10%, and 15% in the systems with spherical zinc. The organic coatings were subjected to accelerated cyclic corrosion tests and electrochemical measurements. The sample containing polyaniline carbonate (PVC = 1%) and spherical zinc exhibited a significantly lower corrosion rate as compared to that of uncoated steel.
Účinky vodivých polymerů (typ a koncentrace) v povlacích s částicemi zinku různých tvarů
Keywords: Conductive polymer; Zinc powder; Lamellar particle; Spherical particle; Coating; Anticorrosion efficiency; vodivý polymer; zinkový prach; lamelární částice; sférická částice; povlak; antikorozní účinost